Localized Pulmonary Interstitial Emphysema Which Occurred After Non-invasive Mechanical Ventilatory Support - Esra Türe; Hakan Ildır; Abdullah Yazar; Fatih Akın; Sevgi Pekcan (Journal of Pediatric Emergency and Intensive Care Medicine, 2020)

(untitled)
Pulmonary interstitial emphysema is a rare condition characterized by collection of air in the pulmonary interstitial tissue outside normal air passages as a result of injury to the alveoli and small airways, and accumulation of air within the perivascular adventitia. In this article, a 5.5-month-old infant who developed pulmonary interstitial emphysema as a result of noninvasive mechanical ventilatory (bilevel positive airway pressure) support in a pediatric intensive care unit, is discussed.